Sosialisasi Pasar Modal Untuk Meningkatkan Minat Mahasiswa Dalam Berinvestasi - Siregar, Zainal Arifin; Prayogi, Oki; Yolanda, Cindy; Butarbutar, Chintya Winda Natalia; Fitri, Melvi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tjut Nyak Dhien, 2025)
This community service aims to improve students' understanding of capital markets and investment and to foster students' interest in investing in order to achieve the government's strategic program and national economic growth through the capital market, which has an important role for the Indonesian economy. This activity was attended by 50 participants from students in the Faculty of Business and Humanities who have taken the Financial Management course. The methods used include the preparation, implementation, evaluation and preparation of reports. The preparation stage begins with conducting an audience and reviewing the place of service implementation, the implementation stage is carried out by socialization and education by matching the prepared material related to the capital market and increasing students' interest in investing and conducting an evaluation after the activity is carried out by looking at the responses of participants with questions and answers. Through this service, it provides an understanding and information about capital market investment products, namely mutual fund investments. Which is an alternative investment in the capital market and is suitable for beginners because it is easy to increase students' interest in investing and is safer.